Antibacterial composition of bioautographic fractions, characteristics, and stability of Carica papaya seed extract - Abdullah Sani, Muhamad Shirwan; Bakar, Jamilah; Abdul Rahman, Russly; Abas, Faridah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2021)
The present work aimed to evaluate the potential of Carica papaya seed extract (CPSE) as an antibacterial agent against Salmonella Enteritidis, Bacillus cereus, Vibrio vulnificus, and Proteus mirabilis. The bioautography of the CPSE on thin-layer chromatography (TLC) plates was performed, followed by fractionation of the CPSE by column chromatography using hexane:ethyl acetate (1:1) eluent. Minimum Inhibitory Concentration (MIC), toxicity, composition, and stability of the crude, fractions, and sub-fractions of the CPSE were evaluated. The bioautographic fractions of the CPSE at MIC of 5.63 mg/mL had shown that hexane:ethyl acetate (1:1) fraction and its sub-fraction 3C (Rf = 0.94 ± 0.03) demonstrated the equivalent MIC value (5.63 mg/mL) with the crude CPSE. However, the hexane:ethyl acetate (1:1) fraction and sub-fraction 3C had higher toxicity (LC50 = 1.797 ± 0.305 and 0.332 ± 0.059 mg/mL, respectively) than the crude CPSE (LC50 = 5.505 ± 0.718 mg/mL). Thus, only the crude CPSE was subjected to stability study. The dominant cis-vaccenic acid in sub-fraction 3C demonstrated the lowest MIC against B. cereus (1.41 mg/mL), P. mirabilis (1.41 mg/mL), and S. Enteritidis (0.70 mg/mL) in its pure form. Hence, these results signified the potency of the cis-vaccenic acid as an antibacterial compound from the CPSE. The stability study of the crude CPSE solution showed that at MIC of 5.63 mg/mL, the crude CPSE solution acted as a potent antibacterial agent in acidic condition (pH 4), water activity (Aw) < 0.950, and temperature < 40°C.